Derivatives of Rhodanine as Potential Antifungal and Antimycobacterial Drugs - Mahmoudi Majd, Morid (2007)
MORID MAHMOUDI MAJD: Derivatives of Rhodanine as Potential Antifungal and Antimycobacterial Drugs". Diploma Thesis, Department of Pharmaceutical Chemistry and Drug Control, Charles University in Prague, Faculty of Pharmacy in Hradec Králové, 2007 Abstract In the theoretical part of my diploma thesis some issues concerning tuberculosis and mycoses are discussed. Experimental part focused on the preparation of the following compounds  5-(2-methoxybenzylidene]-2-thioxo-1,3-thiazolidin-4-one  5-(3-methoxybenzylidene]-2-thioxo-1,3-thiazolidin-4-one  5-(4-methoxybenzylidene]-2-thioxo-1,3-thiazolidin-4-one  5-(4-bromobenzylidene]-2-thioxo-1,3-thiazolidin-4-one  5-pyridin-2-ylmethyliden-2-thioxo-1,3-thiazolidin-4-one. The compounds were prepared by the condensation of rhodanine with aromatic aldehydes in ethanol using a mixture NH4OH/NH4Cl as the catalyst. Their purity was checked by the elemental analysis and HPLC. The products were characterized by IR and NMR spectra. The susceptibility of 8 pathogenic fungal strains (Candida albicans ATCC 44859, Candida tropicalis 156, Candida krusei E 28, Candida glabrata 20/I, Trichosporon asahii 1188, Aspergillus fumigatus 231, Absidia corymbifera 272 and Trichophyton mentagrophytes 445) to these substances was determined by the microdilution broth method. No interesting...